Determinants of Private Equity Buyouts Operating Performance: an empirical investigation in Portugal - Paulo Jorge Costa da Silva (2019)
Despite the consistent increase of private equity (PE) activity in recent years, the bulk of research done have focused on few developed countries, mainly in the United States (US), in the United Kingdom (UK), and in France. Nevertheless, PE are also present in less explored markets, a real growth of this phenomenon has been observed in Portugal. Despite the strong empirical evidence of post-buyout improvements in operating performance for the first buyout wave, particularly in the US, the results for the second buyout wave are less clear. The different results are partially explained by the differences among the two waves, regarding geographic dispersion, leverage levels, and transaction type. Therefore, we examine whether, PE buyouts from the most recent data of Portuguese private-to-private transactions created value and what were its determinants. For a sample of 121 buyouts completed between 2006 and 2016 we show that gains in operating performance are either comparable to or slightly underperform those observed for benchmark firms three years after the deal. Notwithstanding, for a subsample of 31 deals with exit data available gains in operating performance exceed those observed for benchmark firms. More, a relatively recent stream of literature suggests that PE create value by relaxing financial constraints, allowing targets to take advantage of previously unexploited growth opportunities. This complements the well documented literature regarding the stylised fact that PE create value, via agency costs mitigation, trough highly leveraged capital structures. Thus, we find some evidence that leverage, financial constraints and improvements in targets operating performance, appear important in explaining operating gains. PE targets experience a very strong growth in turnover, total assets and operating results, in particular, when they were previously more likely to be financially constrained.